Inside the Politics of Technology : Agency and Normativity in the Co-Production of Technology and Society - Harbers, Hanseauthor (Amsterdam University Press, 2005)
Man is the measure of all things, an old saying goes. But it is a bad guide for understanding scientific and technological culture. Science and technology are not simply the means to reach human ends; they also actively shape human beings, their goals, meanings and social relations. This volume discusses the implications of this so-called 'co-production' of science, technology and society for our analytical as well as normative ideas about humanity, technology and the relations between both. Addressing issues such as cancer genetics, prenatal screening and ecological consequences of traffic and transport, contributors argue that technology has its own kind of sub-politics, which in turn calls for policies of technology: from steering and regulation to scenario studies, in order to achieve democratisation of technology.p‰'De mens is de maat van alle dingen', zo luidt een oud gezegde. Maar die stelling helpt ons niet om de huidige kennismaatschappij en technologische cultuur beter te begrijpen. Wetenschap en technologie zijn immers niet alleen middelen om onze doelen te bereiken; omgekeerd hebben nieuwe wetenschappelijke en technologische ontwikkelingen ook een sterke invloed op mensen, hun wensen en hun onderlinge relaties. Welke consequenties heeft deze zogenaamde 'coproductie' van wetenschap, technologie en samenleving voor onze opvattingen over humaniteit en technologie? Wanneer techniek een sociale, politieke of zelfs morele lading heeft, hoe moeten wij dan omgaan met een 'politiek van de technologie'? Met concrete voorbeelden als het gebruik van videocamera's, electrische auto's en computers tot zwangerschapstesten en genetische screening maken de auteurs inzichtelijk hoe politiek en technologie elkaar beèinvloeden. Met bijdragen van Cornelis Disco, Philip Brey, Nelly Oudshoorn, Margo Brouns, Ellen van Oost, Dirk Stemerding, Annemiek Nelis, Peter-Paul Verbeek, Petran Kockelkoren, Boelie Elzen, Tsjalling Swierstra, Jaap Jelsma en Marcus Popkema.